E-Waste Management in Office Environments: A Systematic Review of Strategies and Challenges - Virda Ramadhani Putri; Tutik Inayati; Ratna Wulandari; Tegar Arrasyid (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
The rapid growth of electronic devices in organizational workplaces has created critical environmental challenges driven by increasing e-waste accumulation. Although office environments contribute substantially to global e-waste generation, existing research remains fragmented, with limited comprehensive synthesis of management strategies, enabling technologies, and implementation barriers. This systematic literature review (SLR) examines e-waste management in office settings, synthesizing evidence across organizational, technological, and policy dimensions. Following PRISMA 2020 guidelines, we searched the Scopus database (October 2025), retrieving 883 documents. After multi-stage screening based on predefined inclusion and exclusion criteria, 80 peer-reviewed articles published between 2020 and 2025 were selected for full-text analysis. Findings reveal that office e-waste is dominated by computing equipment (45–60%), with 30–50% of decommissioned devices stored rather than recycled, primarily due to data security concerns. Effective management strategies encompass Extended Producer Responsibility (EPR) policies, circular economy frameworks, and emerging technologies such as IoT monitoring, blockchain traceability, and AI-assisted sorting. Adoption, however, remains constrained by infrastructure limitations, organizational inertia, stakeholder awareness gaps, and inadequate regulatory enforcement, particularly in developing economies. This review provides the first comprehensive SLR specifically targeting office e-waste management, offering integrated recommendations for organizations, policymakers, and technology providers aligned with ESG and SDG frameworks.